Surfactant Self-Assembling and Critical Micelle Concentration: One Approach Fits All? - Perinelli, Diego Romano; Cespi, Marco; Lorusso, Nicola; Palmieri, Giovanni Filippo; Bonacucina, Giulia; Blasi, Paolo (Langmuir, 2020)
Critical micelle concentration (CMC) is the main chemical-physical parameter to be determined for pure surfactants for their characterization in terms of surface activity and self-assembled aggregation. The CMC values can be calculated from different techniques ( ., tensiometry, conductivity, fluorescence spectroscopy), able to follow the variation of a physical property with surfactant concentrations. Different mathematical approaches have been applied for the determination of CMC values from the raw experimental data. Most of them are independent of the operator, despite not all of the fitting procedures employed so far can be applied in all techniques. In this experimental work, the second derivative of the experimental data has been proposed as a unique approach to determine the CMC values from different techniques (tensiometry, conductimetry, densimetry, spectrofluorimetry, and high-resolution ultrasound spectroscopy). To this end, the CMC values of five different surfactants, specifically three anionic (sodium dodecyl sulfate, sodium deoxycolate, and -lauroyl sarcosinate) and two nonionic, such as polyethylene glycol ester surfactants [polyethylenglicol (8) monostearate and polyethylenglicol (8) monolaurate], have been determined by this approach. The "second-derivate" approach provides a reliable determination of the CMC values among all of the techniques investigated, which were comparable to those calculated by the other operator-free routinely methods employed, such as segmental linear regression or Boltzmann regression. This study also highlighted the strengths and shortcomings of each technique over the others, providing an overview of the CMC values of commonly used anionic and nonionic surfactants in the pharmaceutical field, determined by employing different experimental approaches.